2016
DOI: 10.1186/s12889-016-3680-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural comparison of perspectives on healthy eating among Chinese and American undergraduate students

Abstract: BackgroundUnderstanding views about what constitutes a healthy diet in diverse populations may inform design of culturally tailored behavior change interventions. The objective of this study was to describe perspectives on healthy eating among Chinese and American young adults and identify similarities and differences between these groups.MethodsChinese (n = 55) and American (n = 57) undergraduate students in Changsha, Hunan, China and Honolulu, Hawai’i, U.S.A. composed one- to two-paragraph responses to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…A sizeable proportion of our participants were students in the health fields, and whilst it is anticipated that those would have greater knowledge than other students, there is no evidence to indicate that this knowledge is actually translated into healthy dietary/lifestyle practices [ 26 ]. Hence, views about what constitutes a healthy diet are important, where Chinese and American undergraduate students’ perspectives on healthy eating indicated that understanding the views about what constitutes a healthy diet may inform design of culturally tailored behaviour change interventions [ 38 ]. In agreement, significant differences in dietary patterns were reported between Arabs and Jews in Israel, suggesting a need for culturally congruent dietary interventions to address nutrition-related chronic disease disparities [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sizeable proportion of our participants were students in the health fields, and whilst it is anticipated that those would have greater knowledge than other students, there is no evidence to indicate that this knowledge is actually translated into healthy dietary/lifestyle practices [ 26 ]. Hence, views about what constitutes a healthy diet are important, where Chinese and American undergraduate students’ perspectives on healthy eating indicated that understanding the views about what constitutes a healthy diet may inform design of culturally tailored behaviour change interventions [ 38 ]. In agreement, significant differences in dietary patterns were reported between Arabs and Jews in Israel, suggesting a need for culturally congruent dietary interventions to address nutrition-related chronic disease disparities [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identity (self-concept), social settings, resources, food availability, and other conflicting considerations may explain why people may not be consuming according to their healthy eating ideals [ 40 ]. Hence, across different countries, cultures and environments, such diverse views may reflect food-related messages to which individuals are exposed through the media and through the educational systems in their respective countries [ 38 ]. Future research would benefit from analyses of the relationships between nutritional knowledge, nutrition consciousness, views about what constitutes a healthy diet on the one hand; and the media and how these interrelated factors collectively interact and influence un/healthy nutritional habits in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the general public normally eats three meals a day, thus respondents who ate 2 meals daily and below were categorized as people who ate irregular meals 66 .…”
Section: Methodsmentioning
confidence: 99%
“…What is more and more popular is the trend of the so-called healthy eating (Kapetanaki et al 2014;Banna et al 2016;Rafacz 2019). That trend is mostly associated with the consumption of fresh food products, i.e., vegetables and fruit, grown by local farmers, without artificial fertilizers or plant protection chemicals.…”
Section: Introductionmentioning
confidence: 99%